A new theory of "two-step stabilization mechanism" for triazole-based zinc-containing complex as thermal stabilizer for poly(vinyl chloride). (September 2019) - Wang, Xu; Ma, Biao; Wang, Yating; Lu, Songyan; Ma, Meng; Shi, Yanqin; Chen, Si
Abstract: A totally new theory of "two-step stabilization mechanism" for triazole-based zinc-containing complex (abbreviated as [Zn(ttr)(OAc)]) was proposed through several designed experiments. [Zn(ttr)(OAc)] strongly absorbed HCl at the beginning, and then broke down into 3-amino-1, 2, 4-triazole which could further stabilized PVC. The structure of [Zn(ttr)(OAc)] was characterized by FTIR spectroscopy, elemental analysis and SEM. Then, Congo red tests and discoloration tests verified [Zn(ttr)(OAc)] could absorb HCl effectively, but PVC showed poor initial whiteness, which further proved above-mentioned stabilization mechanism. Moreover, [Zn(ttr)(OAc)] combined with ZnSt2 and dibenzoyl methane (DBM) effectively improved the initial color of PVC samples and provided PVC with shorter plasticizing time and longer dynamic thermal stability time than commercial stabilizer 1086F, confirmed by discoloration tests and dynamic thermal stability analysis. We believe [Zn(ttr)(OAc)]/ZnSt2 /DBM stabilizer system can be used as a commercial stabilizer and the stabilization mechanism of [Zn(ttr)(OAc)] may provide a new way to stabilize PVC. Highlights: A new theory of the "two-step stabilization mechanism" of [Zn(ttr)(OAc)] for PVC was proposed and proved. A novel kind of triazole-based zinc-containing complex with 2D layered frameworks was successfully synthesized. [Zn(ttr)(OAc)] could strongly absorb HCl and prolong the long-term stability of PVC. [Zn(ttr)(OAc)]/ZnSt2 /DBM showed excellent stabilization effect, even compared with commercial stabilizer 1086F. [Zn(ttr)(OAc)] firstly absorbed HCl and then released 3-amino-1, 2, 4-triazole which could still stabilize PVC.